Fecal Incontinence after Severe Brain Injury: A Barrier to Discharge after Inpatient Rehabilitation? - Laura Pelizzari; Elena Antoniono; Donatella Giraudo; Gianluca Ciardi; Gianfranco Lamberti (MDPI AG, 2023)
Background: In this study, we aimed to investigate the incidence of fecal incontinence (FI) after severe acquired brain injuries (sABIs) and to determine whether this symptom can lead to an inability to return home after rehabilitation. Methods: This was a retrospective observational cohort study. In total, 521 acute sABI inpatients were enrolled from the Department of Neurorehabilitation at an academic tertiary care hospital. Patients were divided into two groups, with and without FI, at the end of the rehabilitation phase. The primary and secondary endpoints were the incidence of persistent FI and any difference in the discharge destination. Results: Upon admission, new-onset FI was found in 443 (85%) patients, of which 38% had traumatic sABI. Moreover, 62.7% of all patients had FI upon admission. At discharge, 53.3% (264/495) of patients still had FI. Of these, 75.4% (199/264) had a Rancho Level of Cognitive Functioning Scale (LCFS) ≥3. A statistically significant correlation between FI at discharge and the presence of frontal lesions, autonomic crises, and increased LCFS scores was noted. Among the patients discharged to their homes, the proportion with persistent FI was lower (34% vs. 53.3). Conclusions: FI was significantly persistent after sABI, even after recovery from unconsciousness, and must be considered as a consequence of, rather than an independent risk factor for, unfavorable outcomes.